(untitled) (Economics and region, 2023)
The article presents the results of the research of theoretical foundations and specifies the content of the principles of modeling the assessment of the company’s activity using a balanced system of indicators. The methodological provisions for modeling the assessment of the enterprise’s activity are substantiated. It is recommended to include the following provisions in the list of methodological provisions: 1) content essence; 2) categorical basis; 3) hierarchical structure; 4) feature space; 5) multicriteria; 6) comparative analysis; 7) specification of models; 8) development of strategies; 9) improving the development of a management decision. The proposed theoretical and methodological support for modeling the assessment of the enterprise’s activity based on balanced scorecard allows to assess the state and development of the enterprise’s activity, identify factors for increasing its efficiency, and form decisions regarding strategic management in each type of activity at the enterprise.